Answer:
f(x) = (x - 3)(x + 1) → Corresponds with the first (raised higher ) ∪ shaped graph
f(x) = -2(x - 1)((x + 3) → Corresponds with the ∩ shaped graph
f(x) = 0.5(x - 6)((x + 2) → Corresponds with the second (lower) ∪ shaped graph
Step-by-step explanation:
For the function f(x) = (x - 3)(x + 1)
We have;
When x = 0, y = -3
When y = 0 x = 3 or -1
Comparing with the graphs, it best suits the first ∪ shaped graph that rises here than the other ∪ shaped graph
For the function;
f(x) = -2(x - 1)((x + 3)
When x = 0, y = 6
When y = 0, x = 1 or -3
Which corresponds with the ∩ shaped graph
For the function;
f(x) = 2(x + 6)((x - 2)
When x = 0, y = -24
When y = 0, x = -6 or 2
Graph not included
For the function;
f(x) = 0.5(x - 6)((x + 2)
When x = 0, y = -6
When y = 0, x = 6 or -2
Which best suits the second ∪ shaped graph that is lower than the other (first) ∪ shaped graph
For the function;
f(x) = 0.5(x + 6)((x - 2)
When x = 0, y = -6
When y = 0, x = -6 or 2
Graph not included
For the function;
f(x) = (x + 3)((x - 1)
When x = 0, y = -3
When y = 0, x = -3 or 1
Graph not included
Answer:
Riley rakes 1/4 of the lawns per hour.
Step-by-step explanation:
It is given that,
Riley rakes 1/6 of a lawn in 2/3 hour.
We need to find how many lawns can Riley rake per hour.
In 2/3 hour Riley rakes 1/6 of a lawn
In 1 hour Riley rakes
= 1/4 of a lawn.
Hence, Riley rakes 1/4 of the lawns per hour.
7/12
1/3=4/12
2/3=8/12
7/12>1/3
<span>7/12<2/3
</span>
convert all of these to a common denominator:
7/12 , 1/3 , 2/3
---
7/12 = 7/12
1/3 = 4/12
2/3 = 8/12
---
place into compound inequality:
---
(1/3=4/12) < (7/12=7/12) < (2/3=8/12)